2017
DOI: 10.1097/icl.0000000000000178
|View full text |Cite
|
Sign up to set email alerts
|

Sterile Corneal Infiltrates Secondary to Psoriasis Exacerbations: Topical Tacrolimus as an Alternative Treatment Option

Abstract: Topical tacrolimus may be considered as an alternative treatment option to corticosteroids in sterile corneal infiltrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…The multivariate Cox regression analysis results also reveal age older than 60 and DED as risk factors for keratopathy. These findings are consistent with those of previous research[ 9 11 ] and demonstrate that keratopathy may develop after psoriasis.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The multivariate Cox regression analysis results also reveal age older than 60 and DED as risk factors for keratopathy. These findings are consistent with those of previous research[ 9 11 ] and demonstrate that keratopathy may develop after psoriasis.…”
Section: Discussionsupporting
confidence: 93%
“…Previous reports have revealed cases with concurrent psoriasis and keratopathy. [ 10 , 11 , 20 ] For example, Kilic et al reported on a total of 100 patients with psoriasis, 16 of whom were also diagnosed with keratopathy, including punctate epithelial erosion, vascularization, corneal opacity, and filament keratopathy. [ 10 ] The results of our study are compatible with those of Kilic et al except that our incidence rate is lower.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Psoriasis affects 1–3% of the adult population and is related to multiple extracutaneous manifestations [ 16 ]. Ocular involvement may occur in about 10–20% of cases, is usually bilateral and oftentimes presents in the phase of acute exacerbation [ 17 , 18 ]. Signs and symptoms may be subtle and easily missed during examination.…”
Section: Ocular Changes Associated With Parakeratosismentioning
confidence: 99%